Using the formula for the slope of a line that passes through two given points we get:
![\begin{gathered} m=(-1-2)/(4-0), \\ m=(-3)/(4), \\ m=-(3)/(4)\text{.} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dlq6qcbzg77mfyn7dny4bv1nah26qfzlfo.png)
Now, using the point-slope formula for the equation of a line we get:
![y-(-1)=-(3)/(4)(x-4)\text{.}](https://img.qammunity.org/2023/formulas/mathematics/college/sd3ql2bejidf31olti6usq0xgynwiz0kv4.png)
Taking the above equation to its slope-intercept form we get:
![\begin{gathered} y+1=-(3)/(4)x-(3)/(4)(-4), \\ y=-(3)/(4)x+3-1, \\ y=-(3)/(4)x+2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3g76uybip8n10z17p73twx4crxc53g4qmw.png)
Answer:
The point-slope form is:
![y-(-1)=-(3)/(4)(x-4)\text{.}](https://img.qammunity.org/2023/formulas/mathematics/college/sd3ql2bejidf31olti6usq0xgynwiz0kv4.png)
The slope-intercept form is:
![y=-(3)/(4)x+2.](https://img.qammunity.org/2023/formulas/mathematics/college/djedy5cu6s6dgihr2u09xlujt1spt5vd2q.png)